The possible role of CD8+/Vα7.2+/CD161++ T (MAIT) and CD8+/Vα7.2+/CD161lo T (MAIT‐like) cells in the pathogenesis of early‐onset pre‐eclampsia. (19th December 2017) - Meggyes, Matyas; Szanto, Julia; Lajko, Adrienn; Farkas, Balint; Varnagy, Akos; Tamas, Peter; Hantosi, Eszter; Miko, Eva; Szereday, Laszlo
Abstract : Problem: The objective of this study was to compare the expressions of different immune‐checkpoint molecules by MAIT and MAIT‐like cells in healthy pregnancy and in early‐onset pre‐eclampsia. Method of study: Peripheral blood mononuclear cells (PBMC) were stained with monoclonal antibodies to characterize MAIT and MAIT‐like cells. Flow cytometric analyses were used to measure PD‐1, TIM‐3, activation markers, and intracellular perforin expression. Results: We identified CD3+/CD8+/Vα7.2+/CD161++ MAIT cells and a minor cell population characterized by CD3+/CD8+/Vα7.2+/CD161 lo surface markers. In measuring the expression of PD‐1 receptor, we found a significantly lower expression by MAIT cells in women with early‐onset pre‐eclampsia. CD69 expression by MAIT cells was significantly elevated in early‐onset pre‐eclamptic patients. Intracellular perforin content by MAIT and PD‐1+ MAIT cells was significantly increased in pre‐eclamptic patients compared with healthy individuals. Conclusion: Altered frequency and reduced PD‐1 expression combined together with the elevated perforin content of MAIT cells insinuate their potential roles in the pathogenesis of early‐onset pre‐eclampsia.